2004
DOI: 10.1002/hep.20427
|View full text |Cite
|
Sign up to set email alerts
|

A dual reporter gene transgenic mouse demonstrates heterogeneity in hepatic fibrogenic cell populations

Abstract: Activation of hepatic stellate cells (HSCs) and other resident mesenchymal cells into myofibroblasts expressing alpha smooth muscle actin (␣SMA) and collagen I is a key event in liver fibrogenesis. However, the temporal expression profiles of ␣SMA and collagen I genes in these cells is unknown. To address this question, we studied ␣SMA and collagen ␣1(I) transcriptional patterns in primary cultures of HSCs, and additionally, in an in vivo model of secondary biliary fibrosis using transgenic mice that express t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
180
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(195 citation statements)
references
References 36 publications
9
180
0
6
Order By: Relevance
“…[26][27][28] Other studies have shown that activated HSCs express MMP-13 in vivo 19 and in culture. 29,30 Cytokines, such as IL-1 and TGF-␤, stimulate MMP-13 production in cultured-HSCs, 30,31 which was also found in our study. It is likely the expression and activity of MMPs are regulated by the ECM environment via the integrin and/or DDR2 pathway, [31][32][33][34] and therefore upregulation of MMP-13 is found only in the context of a specific matrix environment, which was recapitulated in the BDL model system.…”
Section: Discussionsupporting
confidence: 85%
“…[26][27][28] Other studies have shown that activated HSCs express MMP-13 in vivo 19 and in culture. 29,30 Cytokines, such as IL-1 and TGF-␤, stimulate MMP-13 production in cultured-HSCs, 30,31 which was also found in our study. It is likely the expression and activity of MMPs are regulated by the ECM environment via the integrin and/or DDR2 pathway, [31][32][33][34] and therefore upregulation of MMP-13 is found only in the context of a specific matrix environment, which was recapitulated in the BDL model system.…”
Section: Discussionsupporting
confidence: 85%
“…Although Cholesterol, iNOS, and liver fibrosis S Anavi et al αSMA staining is commonly used as a marker to evaluate the amount/activity of fibrogenic cells in the liver, recent evidence challenges this paradigm. Magness et al 41 provided in vitro and in vivo evidence that there is heterogeneity in HSCs/ myofibroblasts with regard to gene expression. The study elegantly demonstrated that αSMA and collagen α1(I) are not always coexpressed in fibrogenic cell types.…”
Section: Discussionmentioning
confidence: 99%
“…24,26,27 Viable NPCs were collected by density gradient centrifugation through OptiPrept (Accurate Chemical, Norway), which separates HSCs from NPCs. 4,[28][29][30] Cell fractions were pooled from 2-12 mice. Greater than 95% of the isolated HSC exhibited autofluorescence typical of quiescent cells, as has been reported by others.…”
Section: Isolation Of Primary Murine Liver Cellsmentioning
confidence: 99%
“…A better understanding of the mechanisms that regulate the viability and phenotype of HSC will help to advance this goal because the reversibility of hepatic fibrosis appears to hinge upon the elimination of activated HSC. 2 HSC are thought to be fibroblastic mesenchymal cells 3,4 based upon their robust induction of asmooth muscle actin (a-SMA), matrix molecules, and matrix metalloproteinases during activation. 5 However, these cells also exhibit many neuroendocrine features, including the expression of synaptophysin, glial fibrillary acidic protein (GFAP), neural cell adhesion molecule, nestin, 6 neurotrophins, 7 dopamine-b-hydroxylase (DBH), and tyrosine hydroxylase.…”
mentioning
confidence: 99%